Minimum coverage regulation in insurance markets - Daniel McFadden; Carlos Noton; Pau Olivella (SERIEs - Journal of the Spanish Economic Association, 2015)
We study the consequences of imposing a minimum coverage in an insurance market where enrollment is mandatory and agents have private information on their true risk type. If the regulation is not too stringent, the equilibrium is separating in which a single insurer monopolizes the high risks while the rest attract the low risks, all at positive profits. Hence individuals, regardless of their type, "subsidize" insurers. We study the consequences of imposing a minimum coverage in an insurance market where enrollment is mandatory and agents have private information on their true risk type. If the regulation is not too stringent, the equilibrium is separating in which a single insurer monopolizes the high risks while the rest attract the low risks, all at positive profits. Hence individuals, regardless of their type, "subsidize" insurers.
Keywords: I13; D82; 330; Health insurance; Mandatory enrollment; Minimum coverage regulation; Asymmetric information; Market equilibrium; Cross-subsidization